The Writer's advisor - Alkire, Leland G.; Westerman, Cheryl I. (Book Tower Gale Research, 1985)
"A guide to books and articles about writing novels, short stories, poetry, dramatic scripts, screenplays, magazine articles, biographies, technical articles and books, as well as a guide to information about literary agents, marketing, and a wide range of legal and business materials of interest to full and part-time writers."
Keywords: Authorship -- Bibliography